The Advanced Placement Expansion of the 1990s:How Did Traditionally Underserved Students Fare? - Klopfenstein, Kristin (Education Policy Analysis Archives, 2004)
The College Board’s Advanced Placement (AP) Program, which allows students to take college-level courses while in high school, enjoyed tremendous growth in the 1990s. Despite overall growth, small rural schools and high poverty schools continue to offer relatively few AP courses, and black, Hispanic, and low income students remain grossly underrepresented in AP classes. During the 1990s, AP incentive programs primarily subsidized test fees for low income students, but this provided no incentive for low income and rural schools to expand their AP course offerings and did nothing to strengthen the weak academic preparation of low income, black and Hispanic students. Recent federal funding changes provide a step in the right direction by supporting a comprehensive approach to increasing the AP access and participation of traditionally underserved students.